MUTU PENDIDIKAN DAN PEMERATAAN PENDIDIKAN DI DAERAH - Muhammad Idrus (PSIKOPEDAGOGIA Jurnal Bimbingan dan Konseling, 2012)
All countries in the world realize the importance of education that aims to provide guidancefor the survival of a nation. Four things that become a major focal point in improving theeducation, the distribution of education, quality of education, educational relevance, and efficiencyof education management. Increased done should be done thoroughly, not one by one, and otheraspects are ignored .. However, education quality and equity of education in Indonesia is stilllagging behind other countries. One sat improve the quality of education conducted by the State ofIndonesia is to set the standard national examination, but still problematic. Then EquitableEducation conducted also been a problem with unequal education kualutas in each area. It isnecessary to improve education quality and equity of education in Indonesia. It is necessary stepsto address the education problem, namely by directed at improving the quality of education invarious aspects, and improving education performed evenly in each area.